Analysis Of The Influence Of Business Location, Business Capital and Digital Marketing On Business Income - Victor Victor; Iventura Fitra Uli Tamba; Nadya Caroline (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research was conducted in PT. Autostar Mandiri Teknotama Medan with the aim of analyzing the influence of business location, business capital and digital marketing partially and simultaneously on business income.The research population is 65 consumers who come and buy four-wheeled vehicle spare parts products from the company. The research sample uses a saturated sample so the total sample is 65 respondents. The type of data used is primary data and the data source uses secondary data. Data collection techniques use questionnaires, observation and documentation. Data analysis techniques are descriptive statistics, data quality testing, classical assumption testing, multiple regression analysis, hypothesis testing and coefficient of determination using the SPSS program. The research results show that business capital and digital marketing partially have a positive and significant effect on business income in the company, while business location does not have a significant effect on business income. Simultaneously, business location, business capital and digital income have a significant effect on business income.There is a very strong correlation between business location, business capital and digital marketing on company business income. Business income in the company can be explained by business location, business capital and digital marketing at 67.4% and the remaining 32.6% can be explained by other variables that were not studied such as distribution, price, service, marketing communications and so on.